Fidelity of Cloud Emulators: The Imitation Game of Testing Cloud-based Software - , Anna Mazhar; , Saad Sher Alam; , William Zheng; , Yinfang Chen; Nath, Suman; , Tianyin Xu (International Conference on Software Engineering (ICSE), 2025)
Modern software projects have been increasingly using cloud services as important components. The cloud-based programming practice greatly simplifies software development by harvesting cloud benefits (e.g., high availability and elasticity). However, it imposes new challenges for software testing and analysis, due to opaqueness of cloud backends and monetary cost of invoking cloud services for continuous integration and deployment. As a result, cloud emulators are developed for offline development and testing, before online testing and deployment. This paper presents a systematic analysis of cloud emulators from the perspective of cloud-based software testing. Our goal is to (1) understand the discrepancies introduced by cloud emula- tion with regard to software quality assurance and deployment safety and (2) address inevitable gaps between emulated and real cloud services. The analysis results are concerning. Among 255 APIs of five cloud services from Azure and Amazon Web Services (AWS), we detected discrepant behavior between the emulated and real services in 94 (37%) of the APIs. These discrepancies lead to inconsistent testing results, threatening deployment safety, introducing false alarms, and creating debuggability issues. The root causes are diverse, including accidental implementation defects and essential emulation challenges. We discuss potential solutions and develop a practical mitigation technique to address discrepancies of cloud emulators for software testing.